Effects of Folic Acid Consumption on Newborn Defects and Miscarriage, and Content Uniformity Analysis of Three Different Brands of Folic Acid Tablets Dosage Forms - Mohamed , Adel B; Ali, Azza M; Magid, Samia A (Al-Mukhtar Journal of Sciences, 2019)
There is a recent rise in the number of birth defects. This could be related to folic acid deficiency. Folic acid, as an antioxidant, is an important factor in preventing birth defects during embryonic development. This study, via content uniformity measurements and medical history, aimed to investigate the role of folic acid before and during pregnancy and to measure the content uniformity of different brands of folic acid tablets. The statistical study aimed to determine the relationship between folic acid consumption, miscarriage, and anomalies in newborn babies. The study studied a sample of 300 women based on their medical records. There was no significant effect (p-value = 0.143) of folic acid consumption on the frequency of anomalies. On the other hand, there was a high significant relation (p-value = 0.003) between folic acid consumption and miscarriage. The correlation, principally with miscarriage, coincides with previous studies and highlights the importance of folic acid supplementation before and during gestation. Content uniformity measurements were made on three famous folic acid brands (Folic Acid-Nile, Folicum-Julphar and Wockhardt-UK) available at local pharmacies. Measurements on the three folic acid brands were conducted in compliance with the British Pharmacopoeia (BP) (2010) test for content uniformity. Ten tablets from each brand were tested using the UV spectrophotometric method. The results showed that only the first brand name passed the content uniformity test, while the other two brands did not comply with the standards. This result highlights the problem of under-dosing in commercially available folic acid dosage forms, and identifies the need for taking action towards the implementation of quality control on all medical drugs.